2015
DOI: 10.4028/www.scientific.net/amr.1125.421
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characteristic of Hydroxyapatite Synthesized from Cuttlefish Bone by Precipitation Method

Abstract: Calcium phosphates ceramics such as a hydroxyapatite have composition and structure similar to be mineral component of bone. Hydroxyapatite could be production from natural and chemical source with various techniques. In this study, Calcium phosphates was prepared and characterized for future applications on the utilization of bioactivity and resorbability of Hydroxyapatite. Hydroxyapatite was synthesized by precipitation method using cuttlefish bone as the calcium (Ca) source in the form of calcium nitrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…Produksi hidroksiapatit berbasis limbah cangkang sotong telah dilakukan beberapa penelitian di antaranya menggunakan metode kalsinasi dengan variasi suhu 900°C, 1.000°C, 1.100°C 3 jam dan perlakuan waktu Ball milling berkisar 1-3 jam (Solechan dan Rubijanto 2015), presipitasi kimia menggunakan HCl selama 10-12 jam (Faksawat et al 2015) dan hidrotermal pada suhu 200°C selama 24 jam (Tkalcec et al 2014), namun beberapa metode tersebut memiliki beberapa kelemahan yakni membutuhkan waktu kalsinasi yang cukup lama, sulit mendapatkan stoikiometri hidroksiapatit yang diinginkan dan masih terdapat unsur pengotor berupa ion karbonat. Berdasarkan permasalahan tersebut maka perlu dilakukan suatu upayah terkait penggunaan metode ekstraksi hidroksiapatit yang dapat menyerderhanakan kompleksnya produksi hidroksiapatit, salah satunya menggunakan kombinasi metode hidrotermal dan kalsinasi.…”
Section: Pendahuluanunclassified
“…Produksi hidroksiapatit berbasis limbah cangkang sotong telah dilakukan beberapa penelitian di antaranya menggunakan metode kalsinasi dengan variasi suhu 900°C, 1.000°C, 1.100°C 3 jam dan perlakuan waktu Ball milling berkisar 1-3 jam (Solechan dan Rubijanto 2015), presipitasi kimia menggunakan HCl selama 10-12 jam (Faksawat et al 2015) dan hidrotermal pada suhu 200°C selama 24 jam (Tkalcec et al 2014), namun beberapa metode tersebut memiliki beberapa kelemahan yakni membutuhkan waktu kalsinasi yang cukup lama, sulit mendapatkan stoikiometri hidroksiapatit yang diinginkan dan masih terdapat unsur pengotor berupa ion karbonat. Berdasarkan permasalahan tersebut maka perlu dilakukan suatu upayah terkait penggunaan metode ekstraksi hidroksiapatit yang dapat menyerderhanakan kompleksnya produksi hidroksiapatit, salah satunya menggunakan kombinasi metode hidrotermal dan kalsinasi.…”
Section: Pendahuluanunclassified
“…Also, the presence of these ions is reported to facilitate rapid bone regeneration . Sea urchins ( Brissus latecarinatus ), sputnik sea urchin ( Phyllacanthus imperialis ), sea snail (Trochidae Infundibulum concavus ), eastern oyster ( Crassostrea virginica ), conch shells ( Strombus gigas ), giant clam ( Tridacna gigas ), Thunnus obesus bone, sea snail ( Cerithium vulgatum ), land snails ( Helix aspersa , Helix pomatia ), sea snail ( Rapana venosa ), and cuttlefish bone ( Sepia officinalis ) are reported as natural resources of synthesis of HA for biomedical applications. Cuttlefish bone consists of two different layers, dorsal shield and lamellar matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that natural-resource-based raw products are expected to have trace elements like Mg 2+ , Na + , Zn 2+ , Sr 2+ , K + , and Al 3+ , which take part in bioactivity . Cuttlefish-derived HA containing these trace elements also supports faster biomineralization. …”
Section: Introductionmentioning
confidence: 99%
“…HAp can be obtained by two main ways: (1) synthesis from compounds containing calcium and phosphorus [6]; (2) extraction from natural sources including corals [11][12][13], cuttlefish bones [14][15][16][17][18], seashells from clams, oysters, snails [19][20][21][22][23], eggshell [24,25], mammalian bone (e.g. bovine [26,27], camel and horse [28]), fish scales [29][30][31][32], and fish bones [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%